Primary spinal epidural lymphoma: a rare entity with an ambiguous management. Issue 1 (26th January 2020) - Páscoa Pinheiro, João; Rato, Joana; Rebelo, Olinda; Costa, Gonçalo
Abstract : Lymphomas are malignant lymphoid tumours arising from lymphocytic cells. They usually develop in the lymphoid tissues and can spread to other organs; however, primary extra-nodal locations such as the spinal epidural space are less common. The authors report the case of a primary diffuse large B-cell lymphoma of the thoracic spine in a 65-year-old man, who presented to the emergency department with signs of upper motor neuron lesion. The patient underwent surgery in order to decompress the spinal cord. The treatment was concluded with six cycles of chemotherapy with methotrexate, rituximab, cyclophosphamide, vincristine and prednisone followed by radiotherapy. At the 24-month follow-up, no signs of epidural lesion or bone contrast enhancement were observed in thoracic spine MRI. Surgical decompression is recommended in patients with signs of spinal cord injury in order to prevent irreversible neurological damage and is related to high rates of disease-free survival.